A Nantucket Christmas : a novel - Thayer, Nancy, 1943- (New York : Ballantine Books, 2013)
"From the lighthouse sporting a huge wreath to the Christmas Stroll along its quaint streets, holidays on Nantucket are always magical. However, while the town might be aglow like a scene from Dickens tale, unfortunately for newly married island newcomer Nicole Somerset, Christmas means a dreaded visit from her step- daughter. Headstrong Kennedy brings with her a family of her own--husband Archer and adorable 3 year old son, Maddox--but Kennedy's yet to get over her parents' divorce. Pregnant and highly emotional, in an attempt to reconcile her father and mother, Kennedy sets in motion a scheme to sabotage Nicole's meticulous holiday preparations. When Kennedy's glamorous mother appears on the Somerset doorstep, Kennedy thinks her devious plan might just work. Holidays may be a perfect time for reconciliation, but they are also known for miracles. Even before the gifts are unwrapped, other visitors will make unexpected appearances and sweet little Maddox gets his most fervent Christmas wish"--
Keywords: Stepmothers -- Fiction; Stepdaughters -- Fiction; Interpersonal conflict -- Fiction; Families -- Fiction; Nantucket Island (Mass.) -- Fiction; Christmas stories